ANALISIS PASAR UANG ANTAR BANK DI INDONESIA - Corvia Maulidya (Jurnal Ekonomi Pembangunan, 2012)
This research is intended to identify how liquidity of banking influence interbank call money market in Indonesia. Secondary data of the periode 2002 to 2010 are used. The data are analyzed in a qualitatively and quantitatively which is using multiple regression computation of ordinary least sqaure (OLS) and first difference method. The result of this research show liquidity of banking significantly influence interbank money market in Indonesia. Keywords: Liquidity, Interbank Call Money Market, Ordinary Least Square (OLS), and First Difference Method